ASSESMENT OF THE NUTRITIONAL STATUS BASED ON ANTHROPOMETRICAL INDEXES IN CHILDREN AGED 6 FROM NORTH MACEDONIA - Zafirova, Biljana; Trpkovska, Biljana; CHadikovska, Elizabeta; Bojadzieva, Biljana; Dodevski, Ace (Antrophological Society of Serbia- Nis, 2021)
Introduction and Aim: Anthropometry is sensitive, noninvasive and especially important for the assessment of the nutritional status based on anthropometrical indexes in children aged 6 from North Macedonia. Material and methods: We analysed 280 healthy children (140 boys, 140 girls) aged 6 of Macedonian nationality. Six parameters were measured and calculated the following indexes according to the standard formulas: weight-for-age (BW), height-for-age (BH), body mass index-for-age (BMI), mid-upper arm circumferences-for-age (MUAC), waist circumference-for-age (WH) and skinfolds thickness-for-age (SFTr and SFSc). Results: The results showed sex-specific differences in the examined parameters (BW, BH, BMI) in favour of the boys. In contrast, skinfolds thickness (SFTr and SFSc) were significantly higher in girls. The sex-specific difference for the circumferences proved to be insignificant. Values of the 50th percentile in boys were as follows: 24 kg for BW, 119.6 cm for BH, 16.52 kg/m2 for BMI, 17.2 cm for MUAC, 54 cm for WC, 5.2 mm for SFSc, and 8.2 for SFTr. The values in girls were: 22 kg for BW,118cm for BH,15.94 kg/m2 for BMI, 17.6cm for MUAC, 53 cm for WC, 5.8mm for SFSc and 9 for SFTr. Conclusions: These results can be useful as criteria for assessment and detection of deviations in the nutritional status in children aged 6.
Abstract Book, 2021, Anthropological Society of Serbia
Keywords: children; anthropometry; nutritional status